Juridical Analysis of Curator Immunity and Liability in Indonesian Bankruptcy Law - Setiawan, Agus; Nadriana, Lenny (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
This research provides a rigorous, doctoral-level examination of the legal and ethical architecture surrounding curator and administrator immunity within Indonesia’s bankruptcy regime. Employing a normative-juridical methodology enriched by comparative analysis, it interrogates statutory provisions, judicial practices, and professional perspectives to reveal the systemic vulnerabilities arising from Indonesia’s lack of explicit immunity provisions. By juxtaposing Indonesian law with structured immunity models in the United States, the Netherlands, and the United Kingdom, the study demonstrates that functional immunity can serve as a critical mechanism for safeguarding professional independence, provided it is embedded within robust ethical oversight. The research culminates in the proposal of a limited functional immunity model integrated with codified ethical standards and independent supervisory mechanisms. Such reforms would advance legal certainty, reinforce public trust, and align Indonesia’s bankruptcy law with global best practices.